2018
DOI: 10.7717/peerj.5548
|View full text |Cite
|
Sign up to set email alerts
|

Unconscious response inhibition differences between table tennis athletes and non-athletes

Abstract: BackgroundResponse inhibition is associated with successful sporting performance. However, research on response inhibition in athletes from open-skill sports has mainly focused on a consciously triggered variety; little is known about open-skill athletes’ response inhibition elicited by unconscious stimuli.MethodsHere, we explored unconscious response inhibition differences between table tennis athletes (n = 20) and non-athletes (n = 19) using the masked go/no-go task and event-related potentials technique (ER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 43 publications
1
15
0
Order By: Relevance
“…Athletes showed a significant unconscious response priming effect compared to non-athletes, which suggests that athletes exhibited superior unconscious information processing. This finding is consistent with the results of a previous study showing that motor expertise promotes unconscious response inhibition in the general cognitive domain (You et al, 2018). We speculate that motor expertise possessed by athletes facilitates unconscious information processing.…”
Section: Discussionsupporting
confidence: 93%
“…Athletes showed a significant unconscious response priming effect compared to non-athletes, which suggests that athletes exhibited superior unconscious information processing. This finding is consistent with the results of a previous study showing that motor expertise promotes unconscious response inhibition in the general cognitive domain (You et al, 2018). We speculate that motor expertise possessed by athletes facilitates unconscious information processing.…”
Section: Discussionsupporting
confidence: 93%
“…This is especially true in fast sports such as table tennis (TT), which consist of very specific physiological and physical demands [ 6 , 7 , 8 ] and a high contribution of cognitive resources [ 9 ]. These cognitive demands can be linked to the immense time pressure of the game [ 9 ] and the need to stay focused in an open sport environment [ 10 , 11 ]. Research has also shown that TT athletes display faster visuomotor reaction times [ 9 , 12 ], a higher level of executive functions [ 13 ], better unconscious response inhibition [ 11 ] and greater dual task performance [ 14 ] compared to non-athletes, novices or even medium-level TT players.…”
Section: Introductionmentioning
confidence: 99%
“…These cognitive demands can be linked to the immense time pressure of the game [ 9 ] and the need to stay focused in an open sport environment [ 10 , 11 ]. Research has also shown that TT athletes display faster visuomotor reaction times [ 9 , 12 ], a higher level of executive functions [ 13 ], better unconscious response inhibition [ 11 ] and greater dual task performance [ 14 ] compared to non-athletes, novices or even medium-level TT players. However, this important contribution of cognitive skills is not exclusively beneficial, as this may lead to a higher mental load on the individual, which can result in a higher risk of suffering decrements in performance due to mental fatigue (MF) [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Forty-two participants participated voluntarily and received financial compensation after completing all the experiments. In order to find an interaction between expertise and response congruency in line with You et al. (2018) power analysis (G*Power 3.1, α = 0.05, power = 0.80, effect size = 0.24) showed that a minimum 16 volunteers needed to participate.…”
Section: Methodsmentioning
confidence: 94%